Production of the angiotensin I converting enzyme inhibitory peptides and isolation of four novel peptides from jellyfish (Rhopilema esculentum) protein hydrolysate. (30th November 2015) - Liu, Xin; Zhang, Miansong; Shi, Yaping; Qiao, Ruojin; Tang, Wei; Sun, Zhenliang
Abstract: BACKGROUND: Angiotensin I converting enzyme (ACE) plays an important role in regulating blood pressure in the human body. ACE inhibitory peptides derived from food proteins could exert antihypertensive effects without side effects. Jellyfish ( Rhopilema esculentum ) is an important fishery resource suitable for production of ACE inhibitory peptides. The objective of this study was to optimize the hydrolysis conditions for production of protein hydrolysate from R. esculentum (RPH) with ACE inhibitory activity, and to isolate and identify the ACE inhibitory peptides from RPH. RESULTS: Rhopilema esculentum protein was hydrolyzed with Compound proteinase AQ to produce protein hydrolysate with ACE inhibitory activity, and the hydrolysis conditions were optimized using response surface methodology. The optimum parameters for producing peptides with the highest ACE inhibitory activity were as follows: hydrolysis time 3.90 h, hydrolysis temperature 58 °C, enzyme:substrate ratio 2.8% and pH 7.60. Under these conditions, the ACE inhibitory rate reached 32.21%. In addition, four novel ACE inhibitory peptides were isolated, and their amino acids sequences were identified as Val‐Gly‐Pro‐Tyr, Phe‐Thr‐Tyr‐Val‐Pro‐Gly, Phe‐Thr‐Tyr‐Val‐Pro‐Gly‐Ala and Phe‐Gln‐Ala‐Val‐Trp‐Ala‐Gly, respectively. The IC50 value of the purified peptides for ACE inhibitory activity was 8.40, 23.42, 21.15 and 19.11 µmol L −1 . CONCLUSION: These results indicate that the protein hydrolysate prepared from R. esculentum might be a commercial competitive source of ACE inhibitory ingredients to be used in functional foods. © 2015 Society of Chemical Industry